2013
DOI: 10.4995/rlyla.2013.955
|View full text |Cite
|
Sign up to set email alerts
|

Students' response to CLIL in tertiary education: the Case of Business administration and economics at Complutense University

Abstract: The implementation of Content and Language Integrated Learning (CLIL) (Sierra, 2011;Llinares and Whittaker, 2009; Halbach, 2009, inter alia), there is still a considerable lack of studies focusing on the Spanish university context and the attitude of both lecturers and students to the implementation of these EMI courses (Aguilar and Rodríguez, 2012;Dafouz, 2011;Dafouz and Núñez, 2009;Dafouz et al, 2007;Muñoz 2001

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…It is logical as the lecturers do not expose much on grammatical accuracy during the teaching and learning, yet emphasize more on the content. The result of the students' responses on grammar is line with Arevalo & Romero (2013) concluded that grammar accuracy did not benefitted in CLIL classroom because it does not explicitly focus on language issues, yet meaning. However, when the students have to give general reflection, whether or not the implementation of CLIL affects their general ability in English communication, it is surprisingly found that both sides have the equal proportion: 50% students stated No while the other 50% stated Yes.…”
Section: Notesupporting
confidence: 67%
“…It is logical as the lecturers do not expose much on grammatical accuracy during the teaching and learning, yet emphasize more on the content. The result of the students' responses on grammar is line with Arevalo & Romero (2013) concluded that grammar accuracy did not benefitted in CLIL classroom because it does not explicitly focus on language issues, yet meaning. However, when the students have to give general reflection, whether or not the implementation of CLIL affects their general ability in English communication, it is surprisingly found that both sides have the equal proportion: 50% students stated No while the other 50% stated Yes.…”
Section: Notesupporting
confidence: 67%
“…Nigerian English) as appropriate to the context, or a medium of communication as in ELF (Jenkins 2014). Moreover, research which shows that students’ listening skills improved (Maiz-Arévalo & Dominguez-Romero 2013; Aguilar & Muñoz 2014) is not providing evidence of equipping graduates with the linguistic skills they need for their study and future employment, and improved listening skills might be predictable with an increased exposure to English in lectures. One of the weaknesses of the studies reviewed is that any comparison between EMI and EFL provision, in terms of language improvement, has not considered these factors nor carefully controlled for confounding variables in the comparison of the two systems of provision (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The review also noted that while gains in these areas support the purported benefits of and success of content and language integration programs, findings on greater linguistic competence have been mixed. Other authors' findings have been equally varied; some have contended that improvements in grammatical accuracy in the CLIL classroom are lower than those achieved in speaking and listening (Pica, 2010;Maíz-Arévalo & Domínguez-Romero, 2013), while others have found that a CLIL environment offered a better learning ground for linguistic gains than a mainstream language class (Arment & Perez-Vidal, 2015;Lasagabaster & Doiz, 2016). A large scale study of over 1,000 primary and secondary school students in Andalusia by Lorenzo, Casal, and Moore (2010) found CLIL learners outperformed their Non-CLIL peers in overall language proficiency (reading, writing, speaking, and listening) while another longitudinal study of 403 students at a secondary school over a four-year period by Arribas (2016) found no statistically significant advantage in vocabulary gains in students exposed to CLIL via additional hours of instruction compared to their Non-CLIL counterparts.…”
Section: Universidad De La Sabana Department Of Foreign Languages and Culturesmentioning
confidence: 99%